Pendampingan Proses Produksi Sabun Natural Mayangsari di Kelompok Bumdes Desa Pesanggrahan Kota Batu - Sujono Sujono; Dian Indratmi; Hendra Kusuma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Natural soap is a soap with basic ingredients using herbal ingredients such as olive oil, coconut oil, and milk. MayangSari natural soap is produced by a joint business group in the Pesanggrahan Village, Batu City. The problem of natural soap production in the Mayangsari business group is that there is no selling permit from BPOM, the liquid soap production process has not been maximized where it does not yet know the technique of mixing milk with other ingredients so that it is easily separated, lack of equipment so that production is not optimal and bookkeeping management and marketing are still manual. The aim of the Community Service Program (PUBM) is to improve the quantity and quality of etawa goat milk soap, expand the product marketing network, and improve the group's managerial ability. The method used in the Community Service activities includes 4 stages, namely the practice of production, training, mentoring, and product publication. The result of the implementation of the Community Service program is to increase the productivity of the agroindustry of "Olive Milk" etawa goat milk soap, among others through the practice of natural soap production by utilizing grant equipment from DPPM-UMM.